Tecendo tradição: artesanato e mercado simbólico em uma comunidade rural do Pampa Gaúcho - Vargas, Daiane Loreto de (2016)
This study aims to address the issue of crafts and symbolic market, with a view to marketing gauchescos products in the rural community of Vila Progresso artisans in Caçapava do Sul / RS, which initially developed to work with traditional techniques of wool crafts, practiced by generations and transmitted through women. This knowledge in practice produce symbolic pieces of the gaucho way of life of the past, reinvented this Traditionalist Gaucho Movement (MTG) and various contemporary cultural elements, such as the appreciation of the authentic and rustic. From this context, the theoretical study of the thematic guide mentioned the problem of research that sought to investigate: the symbolic mercado of gauchescos products in Vila Progresso in Caçapava do Sul / RS was turning the wool crafts in the community? In this sense, these changes have occurred and have the same consequences for the community of artisans? As a goal, we try to understand the relationships that are established between craft and symbolic gauchescos market products in the affected community, as well as the possible changes that may have occurred because of this relationship and its implications for the community. This research is part of a qualitative methodology, set up as a case study, with exploratory, descriptive and reflective perspective, where the main theoretical and methodological foundations are based on Bourdieu authors (2007) Canclini (1983), and Oliven (2006). As a result of research, it is observed that there were several changes in the daily lives of artisans with the expansion of demand for symbolic products of the gaucho tradition, encouraged by traditionalism, at an early date, and the appreciation of local cultures due to a cultural hybridity experienced by contemporary society. The community of artisans began to diversify crafts to be sold in the local stalls, covering a wide variety of agricultural products in wool, leather and wood, with a view to meet the needs of a consumer who has appreciation for rustic or cultivate invented traditions as a result of this fact the craftsmen grew and achieved economic stability with the expansion of this market. Thus, diversification has brought a number of new elements for the productive and commercial aspects of the craftsmen on site, where craftsmen are building new business strategies and expand trade relations, but without losing the authorship of the production process of woolen